GB insar measurement at the åknes rockslide, norway - Kristensen, Lene; Rivolta, Carlo; Dehles, John; Blikra, Lars H. (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"Åknes is a 54 mil. m3 rockslide at Storfjorden, Western Norway. It has the potential to form a devastating tsunami in the fjord, and therefore it is thoroughly investigated and continuously monitored. Five GB InSAR campaigns have been carried out since 2006 in order to investigate the patterns of surface displacement. Here we present the results of these measurements, and compare them with in situ measurements of surface displacement. The data provide detailed information on the displacement fields in the rockslide. The InSAR system is placed opposite the fjord in relation to the rockslide and due to unusually strong atmospheric disturbance, a statistical filter needs to be applied to the signal when processing. Therefore the data is not included in the early warning system, but in 2012 another GB InSAR system was installed at a different site, which focus on the upper and most active part of the rockslide - and this will be used for early warning in critical phases of the rockslide monitoring, such as during accelerated movement or after a partial collapse."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Åknes is a 54 mil. m3 rockslide at Storfjorden, Western Norway. It has the potential to form a devastating tsunami in the fjord, and therefore it is thoroughly investigated and continuously monitored. Five GB InSAR campaigns have been carried out since 2006 in order to investigate the patterns of surface displacement. Here we present the results of these measurements, and compare them with in situ measurements of surface displacement. The data provide detailed information on the displacement fields in the rockslide. The InSAR system is placed opposite the fjord in relation to the rockslide and due to unusually strong atmospheric disturbance, a statistical filter needs to be applied to the signal when processing. Therefore the data is not included in the early warning system, but in 2012 another GB InSAR system was installed at a different site, which focus on the upper and most active part of the rockslide - and this will be used for early warning in critical phases of the rockslide monitoring, such as during accelerated movement or after a partial collapse.